2009
DOI: 10.1021/bi900426d
|View full text |Cite
|
Sign up to set email alerts
|

Probing Protein Folding Using Site-Specifically Encoded Unnatural Amino Acids as FRET Donors with Tryptophan

Abstract: The experimental study of protein folding is enhanced by the use of nonintrusive probes that are sensitive to local conformational changes in the protein structure. Here, we report the selection of an aminoacyl-tRNA synthetase/tRNA pair for the cotranslational, site-specific incorporation of two unnatural amino acids that can function as fluorescence resonance energy transfer (FRET) donors with Trp to probe the disruption of the hydrophobic core upon protein unfolding. l-4-Cyanophenylalanine (pCNPhe) and 4-eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
160
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(163 citation statements)
references
References 54 publications
(83 reference statements)
2
160
0
1
Order By: Relevance
“…[13][14] Expression of a GFP gene interrupted by an amber codon at site 150 in the presence of pDule-Tet2.0 was efficient and dependent on the presence of Tet-v2.0 (Fig. 1C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14] Expression of a GFP gene interrupted by an amber codon at site 150 in the presence of pDule-Tet2.0 was efficient and dependent on the presence of Tet-v2.0 (Fig. 1C).…”
mentioning
confidence: 99%
“…13 Ninety-six colonies assessed for Tet-v2.0-dependent expression of GFP, contained seven clones that had significant GFP-Tet-v2.0 expression in the presence of Tet-v2.0 and no detectable GFP fluorescence over background in the absence of Tet-v2.0 (Sup. Fig.…”
mentioning
confidence: 99%
“…The kinetics of formation of specific key sub-domain structures should be probed directly, in situ, on the background of the rest of the chain, where mutual influences exist. The possible significance of the loop closure effect in folding in vivo is an intriguing question that might be addressed with currently available FRET and timeresolved fluorescence methods [77,[211][212][213][214]. Co-translational folding of nascent polypeptides on the ribosome is a subject of a major field of current research.…”
Section: Resultsmentioning
confidence: 99%
“…Miyake-Stoner et al reported a smFRET method to probe the disruption of hydrophobic core upon protein unfolding [71]. More recently, Woori Bae et al demonstrated a smFRET approach to unveil the kinetics of multiple protein-protein interactions occurring far below the diffraction limit [72].…”
Section: Detection Of Protein Foldingmentioning
confidence: 99%